Water adsorption on various metal organic framework - Teo, Benjamin How Wei (2018)
In this paper, Metal Organic Framework (MOF) undergoes N2 and water adsorption experiment to observe how the material properties affects the water sorption performance. The achieved N2 isotherms is used to estimate the BET surface area, pore volume and, most importantly, the pore size distribution of the adsorbent material. It is noted that Aluminium Fumarate and CAU-10 has pore distribution of about 6Å while MIL-101(Cr) has 16 Å. The water adsorption isotherms at 25°C shows MIL-101(Cr) has a long hydrophobic length from relative pressure of 0 ≤ P/Ps ≤ 0.4 with a maximum water uptake of 1kg/kg sorbent. Alkali metal ions doped MIL-101(Cr) reduced the hydrophobic length and maximum water uptake of original MIL-101(Cr). Aluminium Fumarate and CAU-10 has lower water uptake, but the hydrophobic length of both materials is within relative pressure of P/Ps ≤ 0.2. The kinetic behaviour of doped MIL-101(Cr), Aluminium Fumarate and CAU-10 are faster than MIL-101(Cr).